Um teto para Carolina e Maura? Crítica à forma de vida capitalista na narrativa autobiográfica de escritoras brasileiras - Macêdo, Stefanie de Almeida (2022)
Developed in the Subjectivity and Criticism of the Contemporary Research Line of the Graduate Program in Psychology at the Federal University of Ceará (UFC), this master's research had as its primary objective the reflection on the character of criticism of the capitalist form of life and of expression of feelings of injustice present in the autobiographical narratives of Carolina Maria de Jesus and Maura Lopes Cançado, written in diaries between the 1950s and 60s. To this end, the notions of narration, writing, forms of life, gender, invisibility, feelings of injustice, and intersectionality, among others, were discussed in the dissertation to understand how the first-person expression of brazilian women in adverse conditions manifests itself in order to represent the horizon of a struggle for social recognition. It is a research that starts from the reflections developed mainly from the tradition of thinking of the critical theory of society, but that is also based on the contributions of literary theories and gender studies to conceive the way in which the experiences of these women are built on the margins of society and of the word, developing these ideas and narratives from the methodology of constellations. In this process, the intersections between conditions of gender, race, class, citizenship status and mental health in a country with hetero-patriarchal colonial roots that manifest themselves as the authors narrate their daily lives were revealed. Throughout this investigation, we realized that, through the first-person accounts of their experiences, and their perceptions of reality, Carolina and Maura reveal portraits of Brazil, who knows, even more faithful than it was, until then, conceived sociologically under this insignia, considering that Brazilian history (and, consequently, its literature) is heir to a nation project, built from the erasure of differences, mainly of women, people of color and indigenous people.